2016
DOI: 10.1007/s10103-016-2007-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the led therapy on the global DNA methylation and the expression of Dnmt1 and Dnmt3a genes in a rat model of skin wound healing

Abstract: The use of light emitting diodes (LED) as a therapeutic resource for wound healing has increased over the last years; however, little is still known about the molecular pathways associated to LED exposure. In the present study, we verified the effects of LED therapy on DNA methylation and expression of the DNA methyltransferase (Dnmt) genes, Dnmt1 and Dnmt3a, in an in vivo model of epithelial wound healing. Male Wistar rats were submitted to epithelial excision in the dorsal region and subsequently distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…However, very few reports demonstrated that DNA methylation is implicated on skin wound healing. For example, decreased level of global DNA methylation is observed in rat skin wound healing 21 . In contrast to DNA methylation, several reports demonstrated the importance of histone modification or histone-modifying enzymes in skin wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…However, very few reports demonstrated that DNA methylation is implicated on skin wound healing. For example, decreased level of global DNA methylation is observed in rat skin wound healing 21 . In contrast to DNA methylation, several reports demonstrated the importance of histone modification or histone-modifying enzymes in skin wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation has been elucidated as a critical molecular mechanism to be of importance to the skin wound healing process and nociceptive sensitization following skin incision [2,26]. Additionally, DNMTs are known to participate in the self-renewal and senescence of human HFSc, which are recognized to be recruited to the skin injury site for further differentiation to repair injured epithelium [27].…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of skin trauma, the basal cells at the edge of the wound begin to proliferate and form a single layer of epithelium, which covers the surface of the granulation tissues of the wound and then differentiate into squamous epithelium [1,2]. Differentiation of epithelial cells is the key process of epidermal wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings may also provide valuable information for wound healing that occurs in other tissues, such as skin, as there may be similar shared mechanisms. 38,39 Although the DNA methylation levels vary in different tissues, the DNA methylation status of specific gene promoters in different individuals is the same. 40 Increasing evidence suggests that epigenetic silencing of miRNA gene expression by CpG hypermethylation is also emerging as a common hallmark of physiological development and specific diseases.…”
Section: Discussionmentioning
confidence: 99%